The Sunni-Shi'a divide : Islam's internal divisions and their global consequences - Betts, Robert Brenton (Potomac Books, 2013)
Until the attacks of September 11, 2001, few Americans knew anything about Islam, let alone about the distinctions between Sunni and Shiæa, the Sufi and Wahhabi, the origins of the Holy QurÆan and Shariæa law, and the respect that all Muslims, even secular ones, harbor for the prophet Muhammad, his family, and Islamic traditions. In The Sunni-Shiæa Divide Robert Betts traces the tortuous history of IslamÆs sectarian divisions, emphasizing the most important one, the Shiæa departure from Sunni ôorthodoxy.ö. Although the majority of Muslims remain faithful to the Sunni sect of Islam, approximately 15 percent subscribe to the Shiæa creed. As AmericaÆs involvement in the Middle East drags on, Betts reiterates that policymakers, scholars, and laymen alike must understand the many faces of Islam, the internal forces in the United States that have brought us into these conflicts, and the role of Israel in the regionÆs escalating tensions. How the increasing hostility between the two main Islamic factions plays out on the world stageuas Sunni Turkey, Shiæa Iran, and their allies vie for dominanceuis of major consequence for everyone, especially financially strapped Europe and the United States.